Clinical efficacy and safety of sirolimus in systemic lupus erythematosus: a real-world study and meta-analysis. (September 2020) - Peng, Liying; Wu, Chanyuan; Hong, Ruping; Sun, Yiduo; Qian, Junyan; Zhao, Jiuliang; Wang, Qian; Tian, Xinping; Wang, Yanhong; Li, Mengtao; Zeng, Xiaofeng
Objective: To provide real-world data and summarize current clinical evidence on the efficacy and safety of sirolimus in active systemic lupus erythematosus (SLE) patients. Methods: This was a prospective real-world clinical study. Included SLE patients should have Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) ⩾ 2. They were treated with sirolimus and followed up regularly. The SLEDAI-2K, Physician Global Assessment (PGA), serological activity indices, and remission of organ manifestations were evaluated. We also performed a meta-analysis to integrate current evidence of sirolimus in SLE. Results: A total of 49 patients were included in the final analysis. After treatment, the SLEDAI-2K (6.2 ± 3.1 versus 4.0 ± 3.4, p = 0.001) decreased significantly, and the prednisone dosage was tapered successfully (9.9 ± 8.8 mg/day versus 5.9 ± 4.0 mg/day, p = 0.002). Serological activity indices also improved [complement 3 (C3): 0.690 ± 0.209 g/l versus 0.884 ± 0.219 g/l, p < 0.001; complement 4: 0.105 ± 0.059 g/l versus 0.141 ± 0.069 g/l, p < 0.001; anti-dsDNA antibody, 200 ± 178 IU/ml versus 156 ± 163 IU/ml, p = 0.022]. The remission proportions of arthritis, skin rash, and thrombocytopenia were 100%, 88.8%, and 46.2%, respectively. A total of 41.2% of lupus nephritis (LN) patients achieved renal remission, but the average 24-h urine protein level was not significantly changed. Meta-analysis enrolled five studies with 149 patients included, and revealed similar results regarding the changes of SLEDAI-2K [−3.5 (−5.0, −2.1)], C3 [0.224 (0.136, 0.311) g/l] and daily dosage of prednisone [−12.7 (−19.9, −5.6) mg/day]. Conclusion: Sirolimus might be effective and tolerated in SLE. The role of sirolimus in LN requires further study.